GAMBARAN KUALITAS HIDUP DAN KOPING PADA PASIEN HEMODIALISA - Wahyuningsih, Melania; Astuti, Lisweni Aris (Coping: Community of Publishing in Nursing; Vol 10 No 4 (2022): Agustus 2022, 2022)
Patients with Chronic Kidney Disease (CKD) require renal replacement therapy, one of which is hemodialysis. Hemodialysis therapy takes a long time and costs a lot of money, so that it can affect the patients’ psyche, quality of life and coping of the patients. This study was aimed to discover the quality of life and coping of hemodialysis patients at the Regional Public Hospital (RSUD) of Prambanan. This study was a descriptive with cross sectional method. The respondents were 42 hemodialysis patients at RSUD Prambanan. The data were taken using questionnaire. The data were analyzed using percentage frequency distribution. The result of the study on characteristics of respondents were male (52,4%), late elderly age (31%), secondary education level (50%), had occupations (59,5%), and undergone hemodialysis for more than 6 months (92,9%). The quality of life of most of the respondents (52,4%) was good, and almost all of them (97,6%) showed good coping mechanism (adaptive). The quality of life was good and coping mechanism showed adaptive of hemodialysis patients at the Regional Public Hospital (RSUD) of Prambanan.